Transgenerational Adaptation to Heavy Metal Salts in Arabidopsis - Reza Rahavi, Mohammad; Migicovsky, Zoe D.; Titov, Viktor; Kovalchuk, Igor (Frontiers in Plant Science, 2011)
Exposure to abiotic and biotic stress results in changes in plant physiology and triggers genomic instability. Recent reports suggest that the progeny of stressed plants also exhibit changes in genome stability, stress tolerance and methylation. Here we analyzed whether exposure to Ni2+, Cd2+ and Cu2+ salts leads to transgenerational changes in the homologous recombination frequency and in the stress tolerance. We found that immediate progeny of stressed plants indeed exhibit increased recombination frequency. When the progeny of stressed plants was propagated without stress, the recombination frequency changed back to normal. Exposure of plants to heavy metals for five consecutive generations (S1-S5) showed that recombination frequency was maintained at high level. Skipping stress after propagation on 50 mM Ni2+ or Cd2+ for 2-3 generations did not decrease the recombination frequency, suggesting certain acclimation to upregulated recombination. Analysis of the progeny of plants exposed to Cu2+ and Ni2+ showed that the plants had higher stress tolerance to the same heavy metal salts. The tolerance was higher in plants propagated on stress for 3-5 generations, which had longer roots than plants propagated on heavy metals only for 1-2 generations. Also the tolerance was more prominent upon exposure to higher concentration of salts. The progeny of stressed plants was also more tolerant to NaCl and MMS.